Relation Between the Incidence of Carotid Artery Calcification and Systemic Diseases - Agacayak KS (Dove Medical Press, 2020)
Kamil Serkan Agacayak,1 Rıdvan Guler,1 Pınar Sezgin Karatas2 1Department of Oral and Maxillofacial Surgery, Dicle University School of Dentistry, Diyarbakır, Turkey; 2Department of Radiology, Diyarbakir Pediatrics Hospital, Diyarbakır, TurkeyCorrespondence: Kamil Serkan AgacayakDicle University School of Dentistry, Department of Oral and Maxillofacial Surgery, Diyarbakır 21280, TurkeyTel +90 412 2411017/3364Email serkanagacayak@gmail.comBackground: The aim of this study is to investigate the relationship of carotid artery calcifications detected in panoramic radiographs of patients aged 60 or older with isolated systemic diseases.Patients and Methods: From October 2018 to December 2019, 867 panoramic radiographs of patients, who applied to Dicle University Faculty of Dentistry for various dental reasons, were collected for examination. Of these 867 panoramic radiographs, 444 panoramic radiographs were included in this study. Medical data were collected from the archival records of the dental school.Results: The study population consisted of 240 female (54.1%) and 204 male (45.9%) patients. Their mean age was 66 ± 7.3 (range: 60– 92) years. Only 39 (8.8%) of the 444 patients had atherosclerotic plaques. Of the 39 patients with carotid artery calcification, 13 (33.3%) were male and 26 (66.7%) were female. As a result of statistical analysis, carotid artery calcification compared to other systemic diseases was found to be significantly more common in patients with hypertension (p = 0.009).Conclusion: Carotid artery calcifications detected coincidentally in standard panoramic radiographs of dental patients may be important markers for preventing serious risks such as coronary artery disease, stroke, and death. The relationship between carotid artery calcifications found on dental panoramic radiographs and hypertension was significant. Therefore, it seems that detection of carotid artery calcifications on panoramic images of hypertension patients must be considered by dentists.Keywords: panoramic radiograph, carotid artery calcification, systemic diseases